ANALISIS PEMANFAATAN LAHAN PEKARANGAN DI KELURAHAN KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - M. Agum Gumelar; Eri Sayamar; Yulia Andriani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to (1) find out the characteristics of the society of the utilization yard in Maharatu Village, Marpoyan Damai District, Pekanbaru City (2) to find out the pattern of the yard Maharatu Village, Marpoyan Damai District, Pekanbaru City. This research was conducted in Maharatu Village, Marpoyan Damai District, Pekanbaru City, from November 2017 to August 2018 using snowball sampling. The number of samples in this study amounted to 20 people, where all samples used the yard. Data analysis used in this study is descriptive analysis. The results of this study indicate: (1) the yard is a plot of soil where there is a place to live and can be planted with useful plants (2) The pattern of yard use of respondents in Maharatu Village is that the whole uses a horizontal pattern (100%) and there were no respondents in Maharatu Village who used the verticulture pattern, the respondents planted the plants directly on the ground / pots in the yard.Keywords: yard, Society, yard pattern.